2018
DOI: 10.1088/1361-648x/aacd86
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen in beryllium oxide investigated by DFT: on the relative stability of charged-state atomic versus molecular hydrogen

Abstract: The behavior of hydrogen in perfect wurtzite beryllium oxide is herein investigated by means of electronic structure calculations based on density functional theory. The formation energies of the following set of states of hydrogen (H, H, H, H, [Formula: see text], [Formula: see text]) are computed and their solubility is established as a function of temperature and pressure with emphasis given to conditions relevant for hydrogen-implanted materials. It is found that all magnetic states H, [Formula: see text],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 60 publications
4
23
3
Order By: Relevance
“…Still, a few years ago, H2 was found stable with a very narrow range of stability in ZnO [34]. Hodille et al also found molecular hydrogen to be quite stable in BeO [35]. As far as zirconia is concerned, the possibility to have molecular hydrogen has been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Still, a few years ago, H2 was found stable with a very narrow range of stability in ZnO [34]. Hodille et al also found molecular hydrogen to be quite stable in BeO [35]. As far as zirconia is concerned, the possibility to have molecular hydrogen has been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Raman microscopy method gives information about atomic vibrations, and is thus able to distinguish chemical bonds in the solids and to reveal how hydrogen isotopes and impurities are bonded, either to metal atoms or to each other's [33,34]. It is particularly sensitive to detect tungsten oxides and the modifications of their characteristic structure and composition after He or D implantation [35][36][37], as well as to detect the presence of H in oxides [38].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as regards the solubility of hydrogen isotopes, the only experimental estimate was carried out on sintered beryllium oxide samples loaded with deuterium 13 . Nevertheless, a few theoretical DFT‐based studies investigated the insertion or diffusion properties of hydrogen in the wurtzite structure 14–17 . The recent work of Hodille 15 extends the work of Marinaupoulos et al 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a few theoretical DFT‐based studies investigated the insertion or diffusion properties of hydrogen in the wurtzite structure 14–17 . The recent work of Hodille 15 extends the work of Marinaupoulos et al 16 . by publishing the solution energies for each chemical state of hydrogen (neutral, charged, molecular) but only the diffusion coefficient of molecular hydrogen was evaluated, 15 while the diffusivity of neutral hydrogen was previously computed by Allouche et al 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation